Leveraging identity to overcome temporal and financial limitations in rapid ethnography in criminological research - Aqil, Nauman (Journal of criminology, 2023)
With limited time and funding, scholars who deploy qualitative methodologies to examine deviance and criminogenic contexts, such as ethnography, must leverage sources of capital which reduce time-arcs and costs needed for qualitative research. Traditional ethnographic projects require both significant time and funding; accordingly, several authors have indicated the utility of ?rapid ethnographies?, which require less time in the field and funding. By reflecting on three rapid ethnographies, we show how identity is simultaneously a property that informs how research unfolds and a capital that can be leveraged to compensate for temporal and financial deficits. In short, we show that rapid ethnography can be conducted ethically and that identity can counterbalance deficits in monetary and temporal capital when identity is carefully considered in the pre-planning and execution of a rapid ethnographic project.